2022
DOI: 10.1101/2022.06.06.22275988
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Workplace infection control measures and perceived organizational support during the COVID-19 pandemic in Japan: a prospective cohort study

Abstract: ObjectiveWe investigated whether workplace infection control measures during the COVID-19 pandemic could increase perceived organizational support (POS).MethodsThis prospective cohort study was conducted in Japan from December 2020 to December 2021 using a questionnaire survey. There were 18,560 respondents at follow-up; we investigated 4,971 who rated low POS at baseline. The participants were asked a single question about POS and nine about workplace infection control measures. We determined the odds ratios … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…When workplace vaccination opportunities were offered, we found that POS increased more among participants with low baseline POS, and decreased less among those with high baseline POS, than when these opportunities were not offered. These changes remained significant when we adjusted for workplace infection prevention measures, suggesting that the effect is independent of the increase in POS resulting from workplace infection prevention measures that was reported in a previous study 8 …”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…When workplace vaccination opportunities were offered, we found that POS increased more among participants with low baseline POS, and decreased less among those with high baseline POS, than when these opportunities were not offered. These changes remained significant when we adjusted for workplace infection prevention measures, suggesting that the effect is independent of the increase in POS resulting from workplace infection prevention measures that was reported in a previous study 8 …”
Section: Discussionsupporting
confidence: 62%
“…In this study, we found that implementing more infection control measures in the workplace was associated with more vaccination opportunities. It has already been reported that proactiveness in workplace infection control measures leads to improved POS 8 . The level of infection control measures in the workplace could therefore have been a confounding factor in the relationship between vaccination opportunities and POS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations